Innovation as a driving factor of economic development - Ristić Nataša; Vukajlović Vladimir; Brazaković Pavle (Ekonomija: teorija i praksa, 2016)
Today it is impossible to imagine the success of economy as a whole, as well as business entities as part of economy, without innovative activities. Every new idea does not necessarily imply success in itself, but must primarily be proved in the market in order to be called innovation. Regardless of the type of business activity or size of business entity, continuous changes and improvement of products, services and processes are crucial for success. Economic activity at the micro level reflects success at the macro level. Innovative activities of economies are measured using the Global Innovation Index and best ranked are high-income economies that invest in research and development. Serbia, as a country with high to medium income, shows a declining trend regarding the Global Innovation Index. On the other hand, Serbia has a better position on the Innovation Efficiency Index, given that this Index neutralizes the differences in economic development between countries. Research conducted on a sample of 433 companies of different sizes and activities shows that innovative activity of enterprises in the sample has been rated with a below average grade, and there was significant difference in the evaluation of innovative activity of enterprises of different sizes and activities.